2017
DOI: 10.12788/jhm.2701
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Safety and Value of Inpatient “Very Important Person” Services

Abstract: Providing care to "very important person" (VIP) patients can pose unique moral and value-based challenges for providers. No studies have examined VIP services in the inpatient setting. Through a multi-institutional survey of hospitalists, we assessed physician viewpoints and behavior surrounding the care of VIP patients. A significant proportion of respondents reported feeling pressured by patients, family members, and hospital representatives to provide unnecessary care to VIP patients. Based on self-reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…patients include the excess ordering of laboratory tests, imaging, and consultations that may not be clinically indicated. 9,3,17,24 V.I.P. care can also result in extended lengths of stay.…”
Section: Issues With Vip Care Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…patients include the excess ordering of laboratory tests, imaging, and consultations that may not be clinically indicated. 9,3,17,24 V.I.P. care can also result in extended lengths of stay.…”
Section: Issues With Vip Care Outcomesmentioning
confidence: 99%
“…services were offered at their hospitals, including special menus, private or luxury-style rooms, and personal care attendants. 17 While these V.I.P. options are common, they are different from the V.I.P.…”
Section: Descriptions Of Vip Carementioning
confidence: 99%
See 2 more Smart Citations
“…To continue Illen Dicker describes there is a pressure associated with the care of these patients, close to 67% of the doctors exposed to the treatment and management of a VIP patient, said to feel an external pressure about the possible outcomes of their patient, and does not act according to the medical logic, In addition to this feeling, the study reported that 56% of the physicians agreed to the demands of the patients regardless of whether they were relevant to their treatment (8). This is where the ethical dilemma of the physicians begins, a struggle between their autonomy and what is justly correct, a struggle between what should be done and what the patient wants to be done.…”
Section: Ethical Aspectsmentioning
confidence: 99%